Who was Charles Darwin? Biography - Easy Reader. - Hopkinson, Deborah, Nancy Harrison; Harrison, Nancy, 1963- (New York : Grosset & Dunlap, 2005)
An introduction to the life and accomplishments of the nineteenth-century British naturalist Charles Darwin.
Who was Charles Darwin? -- An ordinary boy -- Chance of a lifetime -- Charles becomes a scientist -- To the Galapagos -- Secret notebooks -- Down House -- The origins of life -- Charles Darwin's revolution.
Includes bibliographical references (pages 102-104)
Keywords: Darwin, Charles, -- 1809-1882 -- Juvenile literature; Naturalists -- England -- Biography -- Juvenile literature